Kadar 25(OH)D3 darah pada penderita obesitas - Dessy Hermawan; Slamet Widodo (Jurnal Gizi Klinik Indonesia, 2021)
Blood level 25(OH)D3 in obese peopleBackground: Currently, obesity is a world problem, even the World Health Organization (WHO) declared obesity to be a global epidemic and contributes 5% of global deaths in 2015. Recently, many studies have reported an association between vitamin D levels and the incidence of obesity, although the exact mechanism raises many questions.  Objective: This study is to examine the correlation between levels of 25(OH)D3 and body mass index (BMI).Methods: The design of this research is an analytic survey with a case control approach. The population of this study was all students of the Faculty of Medicine, Malahayati University, Bandar Lampung. The number of samples in this study were 60 samples with details of 30 case samples (obesity) and 30 control samples (no obesity). The sampling technique used was purposive sampling. The data used are primary data from direct measurement results. The data were analyzed using the correlation test.Results: The results showed that only one sample had normal 25(OH)D3 levels, while most (more than 98%) had low and very low levels of 25(OH)D3. The correlation test showed that there was a significant relationship between 25(OH)D3 levels with BMI (p=0.008; r= -0.0338), gender (p=0.001; r= -0.457), and total cholesterol levels (p=0.009); r= -0,391).Conclusions: There is a relationship between levels of 25(OH)D3 with BMI, the lower the 25(OH)3 blood level, the higher the risk of increasing BMI. Further research is still needed to ensure that giving vitamin D to obese populations can reduce body weight or BMI.